Aristotle’s Nicomachean Ethics and Politics: Their Common Field of Inquiry and Their Common Reader - Skowroński, Leszek (Peitho. Examina Antiqua, 2016)
The aim of the article is to indicate that there is quite strong support in the text of the Nicomachean Ethics for the argument that its inquiry is “political” rather than “ethical” in character – the textual evidence provides reasons to challenge the traditional belief that Aristotle separated ethics from politics and started the rise of ethics as a new branch of philosophy. In addition, one can posit a hypothesis (and this has already been done) that the reader, whom Aristotle had in mind while writing what we now know as the Ethics, was a politician-lawgiver (and not just any educated Greek or – which is even less probable – any human being). So the reader aimed at in the Ethics is the same as the reader aimed at in the Politics – a politician-lawgiver. The Ethics and the Politics are a two-part but inseparable compound that together make a textbook for a politician-lawgiver. Both parts should be read together because the one cannot be understood correctly (i.e. as closely as possible to the intentions of their author) without the other. Aristotle studies human good not from the point of view of the individual but from the point of view of the human community. The highest human good – the philosopher’s eudaimonia – is achieved not by individual effort (or not fundamentally by that) but as a result of good laws and a well-organized life in a polis.